Readiness to Change is Related to Real-World Walking and Depressive Symptoms in Chronic Stroke. Issue 1 (January 2021) - Miller, Allison; Wright, Tamara; Wright, Henry; Thompson, Elizabeth; Pohlig, Ryan T.; Reisman, Darcy S.
Abstract : Background and Purpose: The transtheoretical model is a health behavior model used to understand an individual's readiness to change their behavior. This study aims to apply the transtheoretical model in understanding a person with stroke's readiness to change their activity level, as it relates to physical capacity, physical health, depressive symptoms, self-efficacy, and daily stepping activity. Methods: This was a cross-sectional analysis of baseline data from a clinical trial. Participants' readiness to change their activity levels was measured via self-report and daily stepping activity was measured using a step activity monitor. Robust regression (M-estimation with robust standard errors) was used to test the relationship between readiness to change and measures of physical capacity (6-minute walk test, self-selected walking speed), physical health (body mass index, age-adjusted Charlson Comorbidity Index), depressive symptoms (Patient Health Questionnaire-9), self-efficacy (Activities-Specific Balance Confidence Scale), and daily stepping (steps per day). Results: A total of 274 individuals were included in the analysis. Adjusted for age, readiness to change was positively related to daily stepping (β = 0.29, P < 0.001) and negatively related to depressive symptoms (β = −0.13, P = 0.01). Readiness to change was not significantly associated with measures of physical capacity, physical health, or self-efficacy. Discussion: These results suggest that individuals with stroke in the later stages of change may demonstrate greater daily stepping activity and lower depressive symptoms compared with those in earlier stages. Conclusions: Understanding the relationship between readiness to change, daily stepping, and depressive symptoms will help clinicians implement appropriate stage-specific intervention strategies and facilitate greater improvement in activity levels. Video Abstract available for more insights from the authors (see the Video, Supplemental Digital Content 1, available at: http://links.lww.com/JNPT/A333 ). Abstract : Supplemental Digital Content is Available in the Text.